Judicial transformations the rights revolution in the courts of Europe - Lasser, Mitchel de S.-O.-L'E. (Oxford : Oxford University Press, 2009)
The importance of fundamental rights is exploding across all areas of law in Europe. Grounded in comparative law and political science, this book explores the causes of the rights revolution, and its impact on European judiciaries.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Court of Justice of the European Communities; Judicial power -- European Union countries; Political questions and judicial power -- European Union countries; European Union countries -- Politics and government